Inventarisasi Tanaman Dan Potensinya Sebagai Agen Fitoremediasi di Kawasan Masjid Raya Al Jabbar Bandung (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2024)
The Al Jabbar Grand Mosque, located in Bandung, West Java Province, has a land area of ​​26 Ha, which is surrounded by a lake and various types of plants in it. Data regarding the types of plants found in the Al Jabbar Grand Mosque area is still minimal, so it is important to package it in the form of an inventory. Plants have various benefits, one of which is as a phytoremediation agent. This research aims to inventory plants in the Al Jabbar Grand Mosque area and their potential as phytoremediation agents based on literature studies. The method used is a qualitative approach method where observations are carried out and interviews are carried out with informants using a purposive sampling method. The data obtained was analyzed with reference to journals and books. The research results showed that there were 80 plant species, from 68 plant genera and from 37 family. There are 11 plant species that have the potential to act as phytoremediation agents in the Al Jabbar Grand Mosque area.